Introduction to investigation's methodology in bioethics, hints for the developmento of an interdisciplinary qualitative protocol - Casas Martínez, María de la Luz (Acta Bioethica, 2008)
Bioethics' advance requires science's support for its development. Bioethics' investigation stems from interdisciplinarity which, of course, complicates its fulfilment. One of the items in conflict for beginners in the investigation field is the establishment ofa protocol. This work pretends to state a general overview about the steps that have to be taken to integrate a protocol based on qualitative investigation.